Perlindungan Hukum Terhadap Perempuan Berhadapan Dengan Hukum Sebelum Dan Sesudah Lahirnya Perma Nomor 3 Tahun 2017 Tentang Pedoman Mengadili Perkara Perempuan Berhadapan Dengan Hukum - Nurhilmiyah, Nurhilmiyah (Universitas Muhammadiyah Sumatera Utara, 2019)
The problem of protection against women is still interesting to research. The rules of legislation that exist so far must continue to ensure its implementation properly and properly. Everyone is the same before laws and legislation prohibits discrimination and guarantees equal protection for everyone from discrimination based on any reason, including gender. It became interesting when the Supreme Court of Indonesia issued a Perma No. 3 year 2017 of the guidelines to prosecute women's issues with the law. The author wants to find answers to the question, how exactly is the legal protection state of women who are conflicted with the law before and after the issuance of Perma No. 3 year 2017.